Spectrophotometric analysis of crown discoloration induced by various intracanal medicaments: An in vitro study - Amishi Amit Parikh; D N Nirupama; D N Naveen; J Sindhu; Mohan Thomas Nainan (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study was to assess discoloration potential of four different intracanal medicaments. Materials and Methods: Thirty single-rooted extracted bovine incisors were sectioned to a standardized root length, accessed, instrumented, and placed with temporary filling and cotton pellet. The specimens were divided into five groups (n = 6): Control group with no intracanal medicament and four groups with the following medicaments, i.e., calcium hydroxide (Ca(OH)2), calcium hydroxide with chlorhexidine (Ca(OH)2 with CHX), triple antibiotic paste (TAP), and silver diamine fluoride (SDF), respectively. Calorimetric evaluation, according to CIE L*a*b* system, was performed at pretreatment, on day 1, 7, 14, and 21. Data were analyzed using One-Way ANOVA and Repeated ANOVA. P <0.05 was considered statistically significant. Results: The greatest color change (ΔE*) was observed at day 21 in TAP group (P < 0.001) followed by SDF group (P < 0.013), whereas Ca(OH)2 and Ca(OH)2 with CHX groups did not induce visible coronal discoloration. Conclusions: Ca(OH)2 and Ca(OH)2 with the CHX groups showed the smallest coronal discoloration during the experimental time, whereas TAP and SDF groups showed the highest coronal discoloration.